2013
DOI: 10.1080/10962247.2013.874380
|View full text |Cite
|
Sign up to set email alerts
|

Migration of polycyclic aromatic hydrocarbons (PAHs) in urban treatment sludge to the air during PAH removal applications

Abstract: In the present study, the amounts of polycylic aromatic hydrocarbons (PAHs) penetrating into air during PAH removal applications from the urban treatment sludge were investigated. The effects of the temperature, photocatalyst type, and dose on the PAH removal efficiencies and PAH evaporation were explained. The sludge samples were taken from an urban wastewater treatment plant located in the city of Bursa, with 585,000 equivalent population. The ultraviolet C (UV-C) light of 254 nm wavelength was used within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The exact cause of PO formation is still unclear. Chalmers claimed that osteogenic cells, induction factors, and a proper environment are required for HO formation 25 . Some researchers surmised that the release of bone morphogenic protein during postoperative or traumatic circumstances played an important role in PO formation 26 .…”
Section: Hypothesis Of Po Formationmentioning
confidence: 99%
“…The exact cause of PO formation is still unclear. Chalmers claimed that osteogenic cells, induction factors, and a proper environment are required for HO formation 25 . Some researchers surmised that the release of bone morphogenic protein during postoperative or traumatic circumstances played an important role in PO formation 26 .…”
Section: Hypothesis Of Po Formationmentioning
confidence: 99%
“…Effect of UV irradiation power and time on PAHs in smoked sausages Electron excitation was actively induced due to UV irradiation of smoked sausages, PAHs were attacked by active electrons in an acyclic reaction, which led to the degradation of PAHs. 14 PAHs are significantly hazardous to humans and the European Food Safety Authority (EFSA) uses PAH4 (BaP, BaA, BbFA and CHR) as a marker to measure food hazards. 23 The variation of BaP, PAH4 and PAH15 contents in smoked sausages irradiated with UV are shown in times ranged from 52.1% to 82.8% at 32 W, indicating a positive correlation between radiation power and time with degradation ability.…”
Section: Resultsmentioning
confidence: 99%
“…UV radiation, which ranges from 100 nm to 400 nm and is subdivided into UVA (315-400 nm), UVB (280-315 nm) and UVC (100-280 nm), 12 has emerged as an effective technology for removing trace organic pollutants in wastewater and soil treatment. For instance, Kennedy et al 13 reported PAHs degradation rates of 41% to 91% when elution water was exposed to dark and UV light conditions for 6 h. Similarly, Karaca et al 14 examined the effect of UV irradiation on sludge and observed a significant reduction in the initial Σ5 PAHs (total of 5 PAHs). Salihoglu et al 15 discovered that when sludge was exposed to UV radiation for 2 h, PAHs were reduced 24-77% and HPAHs underwent significant degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of TiO 2 can enhance TrOC removal, but an excessive addition of the particles causes UV scattering in the suspension and decreases treatment efficiency [146]. UV/TiO 2 has high potential to treat polycyclic aromatic hydrocarbons in particular because it results to minimal evaporation of the compound into air since photodegradation is faster than evaporation [150]. Meanwhile, UV/H 2 O 2 treatment of sludge achieved high removal of natural hormones and bisphenol A (e.g.…”
Section: Uv Oxidationmentioning
confidence: 99%
“…UV only, UV/H 2 O 2 , and UV/TiO 2 ) can result to the removal of TrOCs through oxidative degradation [9,150], and also through the evaporation of volatile or semi-volatile TrOCs when temperature rises during UV irradiation [146,150]. It also has potential to enhance biodegradation by oxidising persistent TrOCs into smaller, more biodegradable products [147].…”
Section: Uv Oxidationmentioning
confidence: 99%